PENANGANAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER TIGA STUDI DI PMB LILIS SURYAWATI SST., M. Kes KABUPATEN JOMBANG - Ruliati, Ruliati (LPPM STIKes Bahrul Ulum Jombang, 2019)
Pregnancy is a series of reproductive processes for normal women. During pregnancy, physiological complaints sometimes arise in pregnancy from the first to the third trimester, one of these complaints is back pain. Usually, complaints arise during pregnancy, the most common complaint is in the third trimester of pregnancy. Among them, back pain is a common complaint, especially in the third trimester when the center of gravity in the body has shifted. The purpose of the study was to determine the increase of back pain in third-trimester pregnant women at Mandiri Practice Lilis Suryawati, SST,., M.Kes Midwife. The design of this study is to use the descriptive method in the form of case studies. The research subjects were two clients of the third trimester of pregnant women with complaints of back pain in the Mandiri Practice Midwife Lilis Suryawati, SST,., M.Kes. Data collection techniques a described narratively and carried out with interview techniques (the results of the history contain the client's identity, main complaints, pregnancy history), observation or physical examination. The results of a case study on the clients of Ny R and Yn W with physiological pregnant women in the third trimester, found one similar problem, namely complaints of back pain. After midwifery care for one month, back pain is reduced from first degree to zero with massage, pregnancy exercises, warm compresses. The conclusion of the case of Ny R and Yn W clients with physiological trimester III pregnant women is that the problem is resolved as expected. Suggestions from this case study are giving Health education so that the client can deal with pain at home.